Comparison of postoperative atrial fibrillation after total coronary revascularization via left anterior thoracotomy and conventional median sternotomy coronary artery bypass grafting - Sural, Sefa; Aslan, Vedat; Mutlu, Deniz; Yeral, Nurettin; Ozcaliskan, Ozerdem; Gokaslan, Gokhan (Frontiers in Cardiovascular Medicine, 2025)
Postoperative atrial fibrillation (POAF) is the most common arrhythmia that occurs after coronary artery bypass grafting (CABG), contributing to increased mortality, morbidity, longer hospital stays, and higher healthcare costs. Total coronary revascularization via anterior thoracotomy (TCRAT) has recently emerged as a minimally invasive alternative to the traditional median sternotomy (MS). In this multicenter retrospective cohort study, 424 patients who underwent elective CABG between 1 January 2022 and 31 December 2024 at three centers were analyzed. Of these, 221 patients received TCRAT and 203 underwent MS. To minimize baseline differences, a propensity score matching of 1:1 was performed based on age, sex, left ventricular ejection fraction (LVEF), left atrial diameter, CHA2DS2-VASc score, systolic pulmonary artery pressure, and baseline β-blocker use. POAF was defined as an episode of atrial fibrillation lasting a minimum of 5 min and confirmed by electrocardiography. Independent risk factors were identified using a multivariate logistic regression analysis. The rate of incidence of POAF was 16.7% in the TCRAT group and 25.1% in the MS group (p = 0.045). After matching, a multivariate analysis showed that the traditional surgical approach, MS, was an independent risk factor for POAF [odds ratio (OR), 6.12; 95% confidence interval (CI), 2.48–15.09; p < 0.001]. Advanced age (OR 1.04, p = 0.019), reduced LVEF (OR 0.95, p = 0.019), longer cross-clamp time (OR 1.07, p < 0.001), higher blood transfusion requirements (OR 1.48, p = 0.004), and diabetes (OR 1.91, p = 0.048) were all identified as independent predictors. Despite longer operative and cross-clamp times, TCRAT was associated with a lower incidence of POAF compared with MS.